2014
DOI: 10.1159/000367651
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Visual Deprivation in Rats Regulates Several Retinal Genes and Proteins, Including Differentiation-Associated Fibroblast Growth Factor-2

Abstract: Little is known about the retinal cellular basis of amblyopia, which is a developmental disease characterized by impaired visual acuity. This study examined the retinal transcripts associated with experimentally induced unilateral amblyopia in rats. Surgical tarsorrhaphy of the eyelids on one side was performed in pups prior to eye opening at postnatal day 14, thereby preventing any visual experience. This condition was maintained for over 2 months, after which electroretinograms (ERGs) were recorded, the reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Huynh et al and Pang et al also stated that the pause of normal postnatal changes and the interruption of the henle layer organization and foveal maturation may cause an increase in foveal thickness in amblyopia 39,40 . A recent study supported this hypothesis, demonstrating that the visual deprivation induced molecular, cellular and functional changes by affecting the postnatal differentiation in the retina 13 . This raises the question of whether there is a change in the macular and RNFL thickness after the treatment.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Huynh et al and Pang et al also stated that the pause of normal postnatal changes and the interruption of the henle layer organization and foveal maturation may cause an increase in foveal thickness in amblyopia 39,40 . A recent study supported this hypothesis, demonstrating that the visual deprivation induced molecular, cellular and functional changes by affecting the postnatal differentiation in the retina 13 . This raises the question of whether there is a change in the macular and RNFL thickness after the treatment.…”
Section: Discussionmentioning
confidence: 76%
“…With the introduction of functional magnetic resonance imaging (MRI), morphological and functional deficits have been presented in the LGN, striate cortex and extrastriate cortex in the humans with amblyopia [7][8][9] . The changes occurring in the retina and optic nerve in the case of amblyopia have been researched from past to present, and there is no approved results have been reached so far [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…FGF2-like molecules may be secreted by neighboring cells, such as the retinal pigment epithelium, and they are involved in retinal development and differentiation [20]. Recent studies have shown that FGF2 plays an important role in the treatment of neuroretinal degeneration, myopia, vitreous lesions and in the protection of photoreceptors from oxidative damage [21]. GRB2 is a cytoplasmic protein that contains the src-homology 3 (SH3) domain flanking two single SH2 domains and plays an important role in the coupling of receptor tyrosine kinases to downstream signaling [22].…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the protein expression of two growth factors in N2a cells in order to identify the direct factors targeting the differentiation of N2a cells treated with CM from the retinas of P5 mice. Among several secreted factors, we focused on TGFβ2 and FGF-2, which promote the survival and differentiation of retinal cells [ 4 , 12 , 22 , 32 ]. TGFβ2 signaling has a neuroprotective effect in the retina, modulates the cell death of progenitors during the development of the vertebrate retina and regulates retinal thickness [ 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%